Analisis Kesalahan Penulisan Kata dan Penggunaan Ejaan pada Artikel Pendidikan dan Implikasi dalam Pembelajaran Bahasa Indonesia - Betaria Sonata Sianturi; Inda Vandiwinata Simaremare; Siti Aisyah; Yosa Martini Gultom; Imelda Juniarta Sijabat (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This article analyzes spelling and spelling errors in educational articles and their implications for Indonesian language learning. The author emphasizes the importance of correct writing and spelling skills, as well as the negative impact of spelling errors on the quality of writing. The research method used is analysis descriptive, with a focus on identifying and classifying errors. Some of the errors found include non-standard spelling, incorrect use of capital letters and punctuation, and errors in word separation. The author also highlights the need for attention to the General Guidelines for Indonesian Spelling (PUEBI) to improve the quality of writing, by providing examples of specific errors such as incorrect use of capital letters at the beginning of sentences and people's names.